Evaluasi Kebijakan dan Strategi Pengelolaan Sampah di Kota Tangerang Selatan - Ayuni Damayanti Putri; Fiona Kirana Oktavia (Syntax Idea)
Increasing population growth with various activities that they carry out daily will have an impact on production waste or waste generated in the life process. The South Tangerang City Government has the problem of limited land for the Final Processing Site (TPA) where the community produces Â± 400 tons of waste per day, even though if waste is managed properly from reduction to handling, land problems are not a big problem. Various strategies ranging from 3R (Reuse, Reuse, and Recycle), Garbage Bank, Composter, Eco-Enzyme, Maggot and so on can be applied to reduce the accumulation of waste which has become a polemic for the City of South Tangerang. The results of this study indicate that the policy evaluation of waste management in South Tangerang City is not good enough because there are several indicators of evaluation criteria that have not been fulfilled from the aspect of (1) Effectiveness, namely the waste reduction and handling program, the benefits have not been felt because there is still a lot of waste generation, (2) Efficiency where the City of Tangerang Selatan still depends on TPA in other cities, (3) Adequacy, limited land for Cipeucang TPA so that new problems arise and limited facilities and infrastructure, (4) Flattening of the waste reduction program has been running among the community and social education regarding waste at the level schools to campuses, (5) Responsiveness, the South Tangerang City Government responds well to policies from the Central Government by doing as much as possible and, (6) Accuracy, not meeting the right indicators because there are still many problems that need to be addressed starting from reducing waste at the household scale ( sources) to regional scale.